A cytological approach to studying meiotic recombination and chromosome dynamics in Arabidopsis thaliana male meiocytes in three dimensions. (4th June 2018) - Hurel, Aurélie; Phillips, Dylan; Vrielynck, Nathalie; Mézard, Christine; Grelon, Mathilde; Christophorou, Nicolas
Summary: During meiotic prophase I chromosomes undergo dramatic conformational changes that accompany chromosome condensation, pairing and recombination between homologs. These changes include the anchoring of telomeres to the nuclear envelope and their clustering to form a bouquet. In plants, these events have been studied and illustrated in intact meiocytes of species with large genomes. Arabidopsis thaliana is an excellent genetic model in which major molecular pathways that control synapsis and recombination between homologs have been uncovered. Yet the study of chromosome dynamics is hampered by current cytological methods that disrupt the three‐dimensional (3D) architecture of the nucleus. Here we set up a protocol to preserve the 3D configuration of A. thaliana meiocytes. We showed that this technique is compatible with the use of a variety of antibodies that label structural and recombination proteins and were able to highlight the presence of clustered synapsis initiation centers at the nuclear periphery. By using fluorescence in situ hybridization we also studied the behavior of chromosomes during pre‐meiotic G2 and prophase I, revealing the existence of a telomere bouquet during A. thaliana male meiosis. In addition we showed that the number of telomeres in a bouquet and its volume vary greatly, thus revealing the complexity of telomere behavior during meiotic prophase I. Finally, by using probes that label subtelomeric regions of individual chromosomes, we revealed differential localization behaviors of chromosome ends. Our protocol opens new areas of research for investigating chromosome dynamics in A. thaliana meiocytes. Significance Statement: It is well known that during meiotic prophase I chromosomes are subjected to structural modifications, however studying their dynamic behavior in Arabidopsis thaliana has been hampered due to current cytological techniques that dismantle nuclear organization. Here we develop a protocol that allows preservation of the 3D organization of meiocytes, revealing the terminal localization of the synapsis initiation centers and the presence of a telomere bouquet.